Church of Deir Mar Tuma: A Roman Tomb Turned into a Church at Saidnaya (Syria) - Çetinkaya, Halûk (Actual Problems of Theory and History of Art, 2017)
Located in a rock-cut cemetery from the Roman period, a house-type burial was converted into a church most probably in the 5th century. Upon gaining fame, it attracted monks, hence it became a skete type monastery. Approximately 30 kilometers north of Damascus, there is a small town of Qalamoun. This town is known for its churches. Amongst them the Church of Our Lady and Hagia Sophia have special places. The Church of Our Lady in Arabic is Sida Naya, but as time passed it was corrupted and started to be pronounced as Said Naya. In and around this town, there are several historical monuments, especially from Roman and Early Byzantine periods. The local construction material is sand stone.The subject of this article is a misidentified Roman burial turned into a church. Syria was one of the most important provinces of the East. For that reason, the presence of Roman military, settlements of soldiers withfamilies and their burials are scattered around the country. Depending on the status of the deceased, burials had different types. One of the most common types was known as “house type” which was mostly used bythe upper middle class. Examples of these can be observed in the places such as Ataman, Qreiyyeh, Jmarrin, Feki, Ghariyyeh Sharqiyyeh, Rimet al Lohf, Majdal, Murduk, Nahit, Amrah, Khazimeh. Outside the city of Qalamoun, on the skirts of the hills in the North, approximately 400 m away from the Church of Our Lady,there are burials hewn out of main rock in the form of a chamber and several freestanding sarcophagi. There is a clear indication in at least one burial, the Roman eagle, which stood for a former military member. The highestposition was reserved for a “house type” Roman burial, probably from the 2nd century AD. Upon legalizing Christianity this structure which measures 7.1 × 4.2 m was converted into a church. Because of its large size, it was mistaken by scholars for a pagan temple. In fact, it was a burial given newfunction upon adding an apse in its eastern section. Later, this structure became part of a monastic complex where monks stayed for seclusion. According to tradition, it also housed the grave and the relics of the saint who spent years there, namely Mar Touma. My intention has been to show an art piece created for one reason, but acquiring a new function and value in later times. This work intends to broaden geographical and time scale and show other examples of similar structures, thus creating a database.
Keywords: house-type burial; Early Christianity; icon of Saidnaya; converted church